2016
DOI: 10.4028/www.scientific.net/kem.718.40
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Modification Properties of Silicone Rubber Using Organic Filler from Golden Apple Snail Shell

Abstract: Silicone rubber room temperature vulcanization (RTV) is widely used as an insulator. This paper aims to improve the electrical and mechanical properties of RTV with organic filler from golden apple snail shells. The processed golden apple snail shells have the particle size of 75 μm. Specimen were made from silicone rubber with an addition of organic filler and inorganic filler for tested under ASTM D638-2a standard. The filler ratio was varying from 0 to 50% by weight with incremental of 5%. Experimental resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 6 publications
4
2
0
Order By: Relevance
“…Aji et al (2002) reported that composites with higher percentage (12% and above) of groundnut shell filler exhibit poor tensile strength, compared to composites reinforced with lower percentage (below 12%) of groundnut shell filler. Since the tensile strength of the composite general increased up to 6% snail shell/groundnut shell fillers reinforcement, it affirmed previous research (Tepsila and Suksri, 2018) results. Tepsila and Suksri (2018) reported that silicone rubber reinforced with golden apple snail shell filler, yielded superior tensile strength compared to silicone rubber reinforced with CaCO 3 .…”
Section: Tensile Strengthsupporting
confidence: 87%
See 2 more Smart Citations
“…Aji et al (2002) reported that composites with higher percentage (12% and above) of groundnut shell filler exhibit poor tensile strength, compared to composites reinforced with lower percentage (below 12%) of groundnut shell filler. Since the tensile strength of the composite general increased up to 6% snail shell/groundnut shell fillers reinforcement, it affirmed previous research (Tepsila and Suksri, 2018) results. Tepsila and Suksri (2018) reported that silicone rubber reinforced with golden apple snail shell filler, yielded superior tensile strength compared to silicone rubber reinforced with CaCO 3 .…”
Section: Tensile Strengthsupporting
confidence: 87%
“…Since the tensile strength of the composite general increased up to 6% snail shell/groundnut shell fillers reinforcement, it affirmed previous research (Tepsila and Suksri, 2018) results. Tepsila and Suksri (2018) reported that silicone rubber reinforced with golden apple snail shell filler, yielded superior tensile strength compared to silicone rubber reinforced with CaCO 3 . Therefore, snail shell and groundnut shell filler can be used as replacement for CaCO 3 in composite production.…”
Section: Tensile Strengthsupporting
confidence: 87%
See 1 more Smart Citation
“…Effective stress transfer in filled-polymer composites is the key strengthening mechanism for tensile strength enhancement. Also, the presence of calcium carbonate in the snail shell particle [ 17 ], which is hard and rigid, enhances the composite's resistance to deformation, thereby impeding dislocation motion. Another contributing factor was the chain interdiffusion and entanglement between the waste plastic and the snail shell particles which aids improvement in tensile strength in agreement with the research carried out by Daramola et al [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the utilization of snail shell particles as reinforcement provides an environmental friendly means of utilizing this animal waste. Snail shell particulate is a potential reinforcement due to the presence of a hard and rigid CaCO 3 phase [ 17 ]. In this study, the viability and environmental feasibility of utilizing snail shell particles as fillers in recycled waste plastic for interior automobile application were investigated.…”
Section: Introductionmentioning
confidence: 99%